(untitled) (Gragoatá, 2016)
This essay describes how the development of two digital projects dealing with the works of the Mexican poet José Juan Tablada affected the nature of the reading and writing practices of the author and other participants. The first project, produced in the years of 1997 and 1998, comprises two CD-ROM’s with two important sets of journalistic chronicles: La Babilonia de Hierro. Crónicas neoyorquinas (1920-1936) (724 chronicles) and México de día y de noche. Crónicas mexicanas (1928-1943) (399 chronicles). The second one resulted in another CD-ROM, José Juan Tablada: letra e imagen (poesía, prosa, obra gráfica y varia documental) (2003), which included Tablada’s graphic archive, his four visual poetry books and other works involving the relationship between word and image. The project also includes a website (www.tablada.unam.mx). The author points out how automated text searches provided by the first CD’s helped in the annotation process of the graphic archive pieces —which encompass watercolors; pencil, charcoal and ball pen drawings; photographs and clippings from reviews and journals—, and how the careful observation of these images revealed information of Tablada’s life and works. This information had remained unattended because the pieces of the archive had been considered almost exclusively in their visual dimension rather than in relation with the literary realm. The author discusses the three modalities of reading —close, hyper and machine reading— proposed by N. Katherine Hayles, in How We Think (2012), and shows how Tablada’s digital research projects lead to practice the two latter reading modalities in a natural and unperceived way. The recollection of the whole experience also demonstrated that hyper reading promoted by the construction of the website resulted in mnemonic modifications that linked the graphic archive images to Tablada’s biographical discourse. ————————————————————————————————— José Juan Tablada Digital e a gênese de uma hiperleitura O presente artigo descreve o modo como o desenvolvimento de dois projetos digitais envolvendo as obras do poeta mexicano José Juan Tablada afetaram a natureza das práticas de leitura e escrita do autor e de outros integrantes da equipe de pesquisa. O primeiro projeto, levado a cabo em 1997 e 1998, compreende dois CD-ROM com duas importantes coletâneas de crônicas jornalísticas: La Babilonia de Hierro. Crónicas neoyorquinas (1920-1936) (724 crônicas) e México de día y de noche. Crónicas mexicanas (1928-1943) (399 crônicas). O segundo resultou em outro CD-ROM, José Juan Tablada: letra e imagen (poesía, prosa, obra gráfica y varia documental) (2003), o qual incluiu o arquivo gráfico de Tablada, seus quatro livros de poesia visual e outras obras envolvendo a relação entre palavra e imagem. O projeto inclui também uma página web (www.tablada.unam.mx). O autor observa como as buscas automáticas de texto, possibilitadas pelo primeiro CD, ajudaram no processo de anotação das peças do arquivo gráfico —o qual compreende aquarelas, desenhos a lápis, carvão e caneta, fotografias e recortes de jornais e revistas—, e o modo como a observação minuciosa dessas imagens revelou informação relativa à vida e obras de Tablada. Essa informação tinha sido desestimada porque as peças do arquivo tinham sido consideradas quase exclusivamente em sua dimensão visual mais do que em relação com o campo literário. O autor discute as três modalidades de leitura —close, hyper e machine reading— propostas por N. Katherine Hayles em How We Think (2012), e mostra como os projetos de pesquisa digital de Tablada envolvem a prática das duas últimas modalidades de um modo natural e imperceptível. O conjunto da experiência demonstrou também que a hiperleitura promovida pela construção da página web resultou em mudanças mnemónicas que ligaram as imagens do arquivo gráfico com o discurso biográfico de Tablada. — Artigo em inglês.